Reliability and Validity of the Berg Balance Scale in the Stroke Population: A Systematic Review. - Kudlac, Megan; Sabol, Joseph; Kaiser, Katelynn; Kane, Cecelia; Phillips, Robert S. (Physical & Occupational Therapy in Geriatrics, 2019)
Aims: The aim of this systematic review is to assemble literature on the reliability and validity of the Berg Balance Scale (BBS) to determine its suitability as a clinical tool in patients post-stroke. Methods: Systematic searches of PubMed, CINAHL, Scopus, and ProQuest were completed. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines were utilized. Methodological quality was assessed using the McGill Mixed Methods Appraisal Tool. Results: A total of 33 articles were included. The BBS was found to have excellent reliability and validity. The scores were predictive of factors contributing to patient function and performance. Fall risk was unable to be strongly predicted from scores. Conclusion: The BBS is a reliable and valid tool to assess balance and functional mobility in the post-stroke population. However, this tool should not be used as a strong predictor of fall risk in the stroke population as the scoring descriptions indicate.